Characteristics of Persons Living With HIV Who Have Informal Caregivers in the cART Age of the Epidemic. (March 2018) - Schnall, Rebecca; Hirshfield, Sabina; Liu, Jianfang; Siegel, Karolynn; Gradilla, Melissa
Abstract : N/A: People living with HIV (PLWH) are aging and many suffer with multimorbidities, making caregiving a relevant and important area of study. The purpose of our study was to understand the occurrence and role of informal caregivers in the current stage of the HIV epidemic. We conducted a Web‐based survey with 1, 373 PLWH to assess: how many had an informal, unpaid caregiver; the type of relationship with the informal caregiver; and the number of hours the caregiver provided support each day. Among respondents, 333 had an informal caregiver. Blacks, those with low income, individuals who ever had an AIDS diagnosis, those with basic cellphone service, and those living with other comorbid conditions were significantly more likely to have an informal caregiver. Given the demographic profile of those PLWH who were most likely to have caregivers, further study is needed to understand the needs of both caregivers and care recipients.